2020
DOI: 10.3390/bioengineering7010015
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Bioethanol Recovery Using Membrane Distillation for Food Waste Fermentation

Abstract: Ethanol is a material that has a high demand from different industries such as fuel, beverages, and other industrial applications. Commonly, ethanol has been produced from yeast fermentation using sugar crops as a feedstock. However, food waste (FW) was found to be one of the promising resources to produce ethanol because it contained a higher amount of glucose. Generally, column distillation has been used to separate ethanol from the fermentation broth, but this operation is considered an energy-intensive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The ethanol yield of 0.32 g/g biomass resulted in a MESP of approximately 0.14 USD/L, which is very low compared to the market price of 0.59 USD/L for ethanol. This is significantly different than the estimate of 0.64 USD/L of ethanol by Intan Shafinas Muhammad and Rosentrater (2020) [57]. Additionally, while FW is classified as a zero-cost raw material for energy production, there are hidden costs associated with management, collection, and sorting, which are major impediments to industrial waste utilization.…”
Section: Gross Energy Outputmentioning
confidence: 66%
“…The ethanol yield of 0.32 g/g biomass resulted in a MESP of approximately 0.14 USD/L, which is very low compared to the market price of 0.59 USD/L for ethanol. This is significantly different than the estimate of 0.64 USD/L of ethanol by Intan Shafinas Muhammad and Rosentrater (2020) [57]. Additionally, while FW is classified as a zero-cost raw material for energy production, there are hidden costs associated with management, collection, and sorting, which are major impediments to industrial waste utilization.…”
Section: Gross Energy Outputmentioning
confidence: 66%
“…Previous study found that by selling these co-products to other industries it could maximize the profit. (Muhammad and Rosentrater 2020a). However, in this study, bio compost was being utilized to generate heat and power by using the CHP system.…”
Section: Methodology Process Modelingmentioning
confidence: 99%
“…Even though the distillation column was identified as an energy-intensive process, the minimum selling price (MSP) value was the lowest compared to the membrane separation process. From the economic analysis, the MSE for FW fermentation without enzymes and 2-step distillation system was found to be $2.41/gal (Muhammad and Rosentrater 2020a). This value is in between corn ethanol price and cellulosic ethanol.…”
Section: Introductionmentioning
confidence: 95%
“…Downstream processing of ethanol requires solid separation and purification which can be analysed in distillation and dehydration. Distillation is considered as an energy-intensive process and accounts for approximately 40% of the energy demand of the process [40,41]. Normally, two different columns are used in the distillation process: a stripper column, in which the ethanol is separated from solids and non-volatile compounds and a rectification column, where ethanol is concentrated near to the azeotropic point.…”
Section: System Boundaries Analysismentioning
confidence: 99%